DIFFERENCE OF WOUND PAIN BETWEEN SIDE LYING AND FOOTBALL HOLD POSITION IN POST-CESAREAN MOTHERS. - Mardasari, Vina; Helina, Siska; Susilawati, Elly (JURNAL IBU DAN ANAK, 2021)
Sectio Caesarea surgery causes pain and results in changes in tissue continuity due to surgery. The pain will cause various problems, one of which is lactation. To support successful breastfeeding, mothers need to know good and correct breastfeeding techniques. There are several types of breastfeeding techniques, including side lying position and foodball hold. The purpose of this study was to determine the difference between side lying position and football hold breastfeeding position on post-section cesarean wound pain in TK IV Army Hospital Pekanbaru. This type of research is quasy experimental with posttest-only research design and statistical test using independent T-test. The samples in this study were 20 postpartum mothers who gave birth by section cesarean (SC) on the second day which were divided into 2 groups, 10 breastfeeding in a side lying position and 10 people in a football hold position. The study was conducted in the Mawar Room of the TK .IV Army Hospital from January to May 2021. The results showed that the average post-section cesarean wound pain in the side lying position group was 4.40 ± 1.075, while in the football hold breastfeeding group was 3, 8 ± 1.033. The results showed that there was no difference between side lying position and football hold on post section cesarean wound pain (p = 0.219). It is recommended that the hospital which is the place for post-cesarean section care for mothers can guide the mother to breastfeed on the second day of the post-cesarean section.